2010
DOI: 10.1155/2010/437528
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Assisted Reproduction Technology on Placental Imprinted Gene Expression

Abstract: We used placental tissue to compare the imprinted gene expression of IGF2, H19, KCNQ1OT1, and CDKN1C of singletons conceived via assisted reproduction technology (ART) with that of spontaneously conceived (SC) singletons. Of 989 singletons examined (ART n = 65; SC n = 924), neonatal weight was significantly lower (P < .001) in the ART group than in the SC group, but placental weight showed no significant difference. Gene expression analyzed by real-time PCR was similar for both groups with appropriate-for-date… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 31 publications
1
12
1
Order By: Relevance
“…Whether the genes identified here can be powerful predictors of birth weight requires a larger study, which is currently underway. Lower average birth weight has been repeatedly reported from ART compared with natural conception (30)(31)(32), and our results may indicate that cumulus biomarkers can identify gametes more likely to result in live birth with improved developmental potential.…”
Section: Discussionsupporting
confidence: 68%
“…Whether the genes identified here can be powerful predictors of birth weight requires a larger study, which is currently underway. Lower average birth weight has been repeatedly reported from ART compared with natural conception (30)(31)(32), and our results may indicate that cumulus biomarkers can identify gametes more likely to result in live birth with improved developmental potential.…”
Section: Discussionsupporting
confidence: 68%
“…In another study investigating epigenetic changes of several imprinted loci, Katagiri et al (42) compared the expression of four imprinted genes known to be associated with fetal growth in placental tissue obtained from phenotypically normal singletons conceived using ART with those that were conceived spontaneously. Imprinted gene expression was found to be similar between ART and spontaneously conceived infants with weights appropriate for gestational age.…”
Section: Methodsmentioning
confidence: 99%
“…However, both ART and spontaneously conceived infants with fetal growth restriction demonstrated suppression of H19, while spontaneously conceived infants born greater than 3500 grams demonstrated enhanced expression of H19. Expression of CDKN1C, an imprinted growth regulatory gene, was suppressed in ART infants with fetal growth restriction (42). This suggests that hypoexpression of maternally methylated imprinted genes H19 and CDKN1C may be related to growth restriction.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, the decreased expression of IGF-2 could be observed in the placenta of IVF/ICSI [12] and the 10.5 dpc placenta of IVF-ET [13]. Similarly, the expression of IGF-2 in pancreas of the fetuses with Type-II diabetes revealed the decrease by 55% [14], which suggests that parental infertility and ART manipulation may interfere with early development of embryos, and result in abnormal pregnancy and offspring defects [15]. De Rycke et al have evaluated potential risks of ART children, and found that ART could lead to the change of epigenetic modification-related genes [16].…”
Section: Introductionmentioning
confidence: 93%